Regulation of micromorphology and proton conductivity of sulfonated polyimide/crosslinked PNIPAm semi‐interpenetrating networks by hydrogen bonding. Issue 10 (19th February 2014) - He, Yao; Geng, Lei; Tong, Cuiyan; Liu, Lingdi; Lü, Changli
<x xml:space="preserve">Abstract</x> The hydrogen bond interaction between cPNIPAm and SPI in the semi‐IPN structure is a crucial factor for regulating the micromorphology and properties of the semi‐IPN proton exchange membranes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>